2022
DOI: 10.3390/polym14173483
|View full text |Cite
|
Sign up to set email alerts
|

Filling-Balance-Oriented Parameters for Multi-Cavity Molds in Polyvinyl Chloride Injection Molding

Abstract: PVC injection molding has constrained temperature and shear rate owing to its temperature sensitivity and high viscosity, as well as its low conductivity. Many challenges are associated with the PVC injection molding process used for producing PVC fittings with a multi-cavity mold. Once filling imbalance occurs, the gates and/or runner of the mold should be changed by machine tools, which is time- and cost-intensive. Using Moldex3D and the Taguchi method, this study reveals an approach to eliminate imbalanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The identification of parameters affecting the formation of warpage of PVC moldings was also addressed by Ahmed et al A mathematical model was developed to regulate warpage before production and minimize losses [80]. Subsequently, Tsai et al, using Moldex3D and the Taguchi method, determined the possibility of eliminating imbalanced filling of multicavity molds for PVC injection molding [81].…”
Section: Polyvinyl Chloridementioning
confidence: 99%
“…The identification of parameters affecting the formation of warpage of PVC moldings was also addressed by Ahmed et al A mathematical model was developed to regulate warpage before production and minimize losses [80]. Subsequently, Tsai et al, using Moldex3D and the Taguchi method, determined the possibility of eliminating imbalanced filling of multicavity molds for PVC injection molding [81].…”
Section: Polyvinyl Chloridementioning
confidence: 99%
“…where p and τ rz are the pressure and the shear stress, respectively. To get the flow velocity of the fluid v z (r) in a cylindrical channel, the calculation procedures starting from Equations ( 2)-( 4) can be found in references [7,14], and will not be reiterated here for compendiousness. Finally, the v z (r) can be expressed by:…”
Section: Rheological Behavior Of Molten Plasticmentioning
confidence: 99%
“…A suitable objective function needs to be defined in advance; otherwise, the result will be unacceptable. The design of the experiment also provides an optimal arrangement solution to a balanced flow type [12][13][14]. For the past decades, most of the runner system designs of an injection mold were implemented by the empirical rule or trial and error approach.…”
Section: Introductionmentioning
confidence: 99%
“…Mahajan and Ulhe [11] reported mould closing speed as the most dominant parameter for obtaining optimal weight using the Taguchi technique of CPVC elbow parts manufactured using injection moulding. Tsai et al [12] used Moldex3D and the Taguchi method for optimising the mould filling rate for injection moulding of PVC and reported that the temperature of the part increased due to the injection rate. Ardestan et al [13] tried to optimise the blush defect in PVC bushings made using injection moulding by using ANN, PSO, and GA.…”
Section: Introductionmentioning
confidence: 99%